Respuesta :

Answer:

a = 1/2 (1 ±sqrt(47))

Step-by-step explanation:

a^2-a+12=0

We will complete the square

Subtract 12 from each side

a^2-a+12-12=0-12

a^2-a=-12

The coefficient of a = -1

-Divide by 2 and then square it

(-1/2) ^2 = 1/4

Add it to each side

a^2 -a +1/4=-12 +1/4

(a-1/2)^2 = -11 3/4

(a-1/2)^2= -47/4

Take the square root of each side

sqrt((a-1/2)^2) =sqrt(-47/4)

a-1/2 = ±i sqrt(1/4) sqrt(47)

a-1/2= ±i/2 sqrt(47)

Add 1/2 to each side

a-1/2+1/2 = 1/2± i/2 sqrt(47)

a =  1/2± i/2 sqrt(47)

a = 1/2 (1 ±sqrt(47))

ACCESS MORE